Lucifer. The complete fourth season [videorecording (DVD)]. - Ellis, Tom, 1978-; German, Lauren, 1978-; Alejandro, Kevin, 1976-; Woodside, D. B. (David Bryan), 1969- (Warner Bros. Entertainment Inc., [2020], 2020)
The charismatic Lucifer Morningstar returns, resurrected after season three's cliffhanger. His unofficial partner in crime-solving and affairs of the heart, LAPD detective Chloe Decker, returns from an extended vacation, taken after she saw Lucifer's devil face for the first time. Lucifer's old flame, original sinner Eve, shows up and tempts Lucifer with her charms. Does she want revenge for her expulsion from Eden or something else entirely? Will things ever be right with Deckerstar again?